Transplant-associated thrombotic microangiopathy in pediatric patients: pre-HSCT risk stratification and prophylaxis - Higham, Christine S. (Blood Adv, 2021)
Transplant-associated thrombotic microangiopathy (TA-TMA) is an endothelial injury syndrome that complicates hematopoietic stem cell transplant (HSCT). Morbidity and mortality from TA-TMA remain high, making prevention critical. We describe our retrospective single-center experience of TA-TMA after pediatric allogeneic HSCT and present a novel pre-HSCT risk-stratification system and prophylaxis regimen. From January 2012 through October 2019, 257 patients underwent 292 allogeneic HSCTs. Prospective risk stratification was introduced in December 2016. High-risk (HR) patients were treated with combination prophylaxis with eicosapentaenoic acid and N-acetylcysteine. The 1-year cumulative incidence of TA-TMA was 6.3% (95% confidence interval [CI], 3.2-9.4). Age ≥10 years, myeloablative conditioning with total body irradiation, HLA mismatch, diagnosis of severe aplastic anemia or malignancy, prior calcineurin inhibitor exposure, and recipient cytomegalovirus seropositivity were found to be pre-HSCT risk factors for development of TA-TMA. Before routine prophylaxis, TA-TMA rates were significantly different between the HR and standard-risk groups, at 28.2% (95% CI, 0-12.7) vs 3.2% (0.1-6.3), respectively (P < .001). After introduction of prophylaxis, the 1-year cumulative incidence of TA-TMA in the HR group decreased to 4.5% (95% CI, 0-13.1; P = .062, compared with the incidence before prophylaxis). Multicenter pediatric studies are needed to validate these risk criteria and to confirm the efficacy of the prophylactic regimen.